Biometric and Physiological Quality of Bracatinga Seeds From Different Mother Trees - Renata Diane Menegatti; Adelar Mantovani; Marcio Navroski (Floresta e Ambiente, 2018)
ABSTRACT Mimosa scabrella Bentham (bracatinga) is a prominent forest species in the south of the country, due mainly to the high rate of increase, rapid development cycle, and to enable multiple uses of wood production, both for firewood and for more noble purposes. The aim of this work was to estimate the physiological variation among 40 mother trees, based on germinative and biometric characterization of seeds and seedlings. Biometric traits were determined for the size and the fresh mass of 100 seeds, percentage of germination and normal seedlings, germination velocity index, daily mean germination, length, and dry mass of seedlings. Means were compared by the Scott-Knott test at 1% probability and estimates of Pearson correlation coefficients were obtained between all traits. The results indicate the existence of significant variation between arrays of same or different origin for both the biometric features as those from the germination test. The physiological quality of the seeds showed no direct relation to its size.